Pengaruh Trust, Perceived Value, dan E-WOM terhadap Keputusan Pembelian pada TikTok Live Commerce di Kalangan Gen Z - Aulina, Dini Septi; Yohana, Corry; Kusworo, Kusworo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the influence of trust, perceived value, and electronic word of mouth (E-WOM) on purchase decisions in TikTok Live commerce among Generation Z. The study is motivated by the rapid growth of live commerce as a digital marketing medium, which has transformed consumer behavior in making purchase decisions, particularly among Generation Z, who are active users of social media and e-commerce platforms. The data used in this study were primary data collected through a Google Forms-based questionnaire distributed to 140 respondents from Generation Z residing in Jakarta who had previously made purchases through TikTok Live commerce. This study employed a quantitative research method with a survey approach. The sampling technique used was non-probability sampling with a purposive sampling method. Data were analyzed using descriptive statistical analysis, validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linear regression analysis, and hypothesis testing through the t-test, F-test, and coefficient of determination (R²). The data were processed using SPSS version 31. The findings indicate that, partially, trust does not have a positive and significant effect on purchase decisions because Generation Z consumers tend to consider the benefits they receive and information from other consumers rather than relying solely on trust in the host or seller. In contrast, perceived value has a positive and significant effect on purchase decisions, and E-WOM also has a positive and significant effect on purchase decisions, as consumers’ perceptions of product benefits and quality, along with reviews and recommendations from other users, increase their confidence in making purchases. Simultaneously, trust, perceived value, and E-WOM have a positive and significant effect on purchase decisions in TikTok Live commerce among Generation Z. The findings of this study reinforce the Consumer decision-making process theory, which explains that purchase decisions are the result of a series of interconnected stages, beginning with need recognition, followed by information search, evaluation of alternatives, and ultimately the purchase decision.